The Mediating Role of Brand Awareness in the Effect of Advertising Appeal on Purchase Intention (A Study on Dear Me Beauty Cosmetic Products) - Ni Kadek Indah Febyanthi; Ni Wayan Ekawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid growth of the beauty industry, particularly in Indonesia, has created a potential market for entrepreneurs while simultaneously intensifying business competition. Aligned with the development of the internet and information technology, companies are encouraged to leverage these advances through advertising on social media, including platforms such as TikTok. One local cosmetic brand that utilizes TikTok for product promotion is Dear Me Beauty. This phenomenon has led to a study that examines the mediating role of brand awareness in the relationship between advertising appeal and purchase intention. The purpose of this research is to analyze the influence of advertising appeal and brand awareness on the purchase intention of Dear Me Beauty’s cosmetic products, and to investigate the mediating role of brand awareness in that relationship. This study was conducted in Denpasar City with a sample size of 100 respondents using a non-probability sampling method and purposive sampling technique. The analysis techniques employed include descriptive analysis and inferential analysis, specifically path analysis and the Sobel test. The results show that advertising appeal has a positive and significant effect on purchase intention; advertising appeal has a positive and significant effect on brand awareness; brand awareness positively and significantly influences purchase intention; and brand awareness mediates the effect of advertising appeal on purchase intention for Dear Me Beauty products.